2005
DOI: 10.1007/s11183-005-0101-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Coordinating Wheat Seedling Growth Response as Affected by Shoot/Root Ratio

Abstract: Excision of four out of five roots in 7-day-old wheat seedlings ( Triticum durum Desf.) rapidly suppressed shoot growth promoted biomass accumulation by the remained root largely due to its expanded branching. Next, the rate of shoot growth increased although was not completely recovered. After the reduction of the root system, the rate of photosynthesis in the leaves of seedlings did not decrease. As compared to the intact plants, auxins and cytokinins accumulated in the remained root, whereas in the growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Physiological mechanisms responsible for rapid growth of lateral shoots, without a corresponding increase in root growth, can promote biomass accumulation ( Vysotskaya, 2005 ). Auxin, an important hormone of shoots, in particular, regulates apical dominance ( Cline et al, 1997 ; Teale et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological mechanisms responsible for rapid growth of lateral shoots, without a corresponding increase in root growth, can promote biomass accumulation ( Vysotskaya, 2005 ). Auxin, an important hormone of shoots, in particular, regulates apical dominance ( Cline et al, 1997 ; Teale et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lower lateral buds can be induced by cutting the terminal bud to remove apical dominance ( Skoog and Thimann, 1934 ; Leyser, 2003 ; Umehara et al, 2008 ). Moreover, the speed of plant shoot growth could be enhanced by lowering the shoot/root ratio ( Vysotskaya, 2005 ), to overcome the space and time limitations. The cutting of lower branches could be a strategy for plant recycling system to speed up the biomass production without the need for further sowing of seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the factors mentioned above initially result in the impairment of the root system and subsequent decline in yield (Ryan et al 2006;Angus et al 2011). Root characteristics are used widely in research on plant reactions in the course of adaptation to stress conditions (Kage et al 2004;Vysotskaya 2005;Alameda et al 2012). However, changes in above-ground growth or yields do not necessarily lead to changes in appearance of the root system (Taylor & Brar 1991;Kopeć & Gła˛b 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Root characteristics are used widely in research on plant reactions in the course of adaptation to stress conditions (Kage et al . 2004; Vysotskaya 2005; Alameda et al . 2012).…”
Section: Introductionmentioning
confidence: 99%
“…After the imbibition, the initial growth (germination process) is followed by substance conversion: from the hydrolysed seed substance into biosynthesised substance of the root and shoot, since the young plant is not capable to produce its own substance by photosynthesis (chlorophyll has not been synthesised or it quantity is under a critical amount). Regarding the fact that the seedling's parts grow unequally (Vysotskaya, 2005;Rauf et al, 2007), which is a particular characteristic of the starting phases of germination, so as their free energy is unequally distributed. Experiments on seed ageing (Dragicevic et al, 2007, Dragicevic, 2007 demonstrated that the highest energy potential of 7-day old seedlings was present on the shoot level, then on the seed rest level and finally on the root level.…”
Section: Growth As Conversion Of Energy and Substancementioning
confidence: 99%